Enantioselective Protonation: Hydrophosphinylation of 1, 1‐Vinyl Azaheterocycle N‐Oxides Catalyzed by Chiral Bis(guanidino)iminophosphorane Organosuperbase. Issue 3 (18th November 2020) - Das, Saikat; Hu, Qiupeng; Kondoh, Azusa; Terada, Masahiro
Abstract: Enantioselective protonation by hydrophosphinylation of diarylphosphine oxides with 2‐vinyl azaheterocycle N ‐oxide derivatives was demonstrated using chiral bis(guanidino)iminophosphorane as the higher‐order organosuperbase catalyst. It was confirmed by several control experiments that a chiral weak conjugate acid of the chiral bis(guanidino)iminophosphorane, instead of achiral diarylphosphine oxides, directly functioned as the proton source to afford the corresponding product in a highly enantioselective manner in most cases. Enantioselective protonation by a weak conjugate acid generated from the higher‐order organosuperbase would broaden the scope of enantioselective reaction systems because of utilization of a range of less acidic pronucleophiles. This method is highlighted by the valuable synthesis of a series of chiral P, N‐ligands for chiral metal complexes through the reduction of phosphine oxide and N ‐oxide units of the corresponding product without loss of enantiomeric purity. Abstract : An enantioselective protonation through hydrophosphinylation of diarylphosphine oxides with 2‐vinyl azaheterocycle N ‐oxide derivatives was demonstrated using chiral bis(guanidino)iminophosphorane. The enantioselective protonation by a weak conjugate acid generated from the higher‐order organosuperbase is promising in enantioselective catalysis because of the utilization of less acidic pronucleophiles.